PENERAPAN METODE VALUE CLARIFICATION TECHNIQUE UNTUK MENINGKATKAN HASIL BELAJAR PKn PADA SISWA KELAS VI DI SDN KEMIRI 01 KECAMATAN PANTI JEMBER SEMESTER DUA TAHUN 2012/2013 - Umi Khasanah (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
As previously described, the research problems can be formulated as follows: (1) how does the implementation of VCT to improve the students’ civic (PKn) learning achievement at class VI SDN Kemiri 01 PantiJember in the even semester of the academic year 2012/2013?; and (2) Is the implementation of VCT able to improve the students’ civic (PKn) learning achievement at class VI SDN Kemiri 01 PantiJember in the even semester of the academic year 2012/2013?.  In accordance with those research problems, this research is aimed at (1) to describe how the implementation of VCT to improve the students’ civic (PKn) learning achievement at class VI SDN Kemiri 01 PantiJember in the even semester of the academic year 2012/2013 is, and (2) know how the students’ civic (PKn) learning achievement is improved using VCT. The research design used was classroom action research. The subjects were the sixth grader students of SDN Kemiri 01 PantiJember. The instruments used to collect data are observation, interview,and questionnaires for students.Descriptive qualitative is employed to analyze the data. The research findings show that it is through the implementation of ASSURE learning model the students’ motivation and learning outcomes in civic education (PKn) for the fourth grader (IV-B) of SDN Jenggawah 01 in odd semester in the academic year 2012/2013 has significantly increased.Keywords : VCT learning model, learning achievement.